Eco-Friendly Synthesis and Characterization of Double-Crossed Link 3D Graphene Oxide Functionalized With Chitosan for Adsorption of Sulfamethazine From Aqueous Solution: Experimental and DFT Calculations - Hamed, Rinad; Jodeh, Shehdeh; Hanbali, Ghadir; Safi, Zaki; Berisha, Avni; Xhaxhiu, Kledi; Dagdag, Omar (Frontiers in Environmental Science, 2022)
Graphene oxide-chitosan composites are attracting considerable interest as an eco-friendly adsorbent material for most of the aquatic environmental pollutants. Today, a focus is on the emergence of 2D and 3D graphene- functionalized with chitosan to enhance its mechanical properties and adsorption efficiency. Herein, the super adsorbent 3D graphene-functionalized with chitosan (3D GF-CS) is synthesized to remove a Sulfamethazine, (SMZ) as a model aquatic antibiotic pharmaceutical. the synthesized materials were characterized through scanning electron microscopy (SEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and X-ray photon spectroscopy (XPS), Brunauer- Emmett –Teller (BET) and Raman spectroscopy. After that, adsorption experiments were conducted for SMZ adsorption to find out the optimized adsorption parameters, like pH, temperature, contact time, initial antibiotic concentration, and adsorbent dosage. The results show the optimal adsorption parameters were as pH of 7, the temperature of 25 °C, and the initial antibiotic concentration Ci of 50 ppm. Also, the kinetics, isotherms models, and thermodynamics parameters of SMZ adsorption were studied. The experimental results revealed to be best suited by both the pseudo-second-order kinetic and the Freundlich isotherm model compared with other isotherm models. The thermodynamics parameters demonstrated that the adsorption is exothermic, exhibiting higher adsorption efficiency at a lower temperature. Besides, Gibb's free energy suggested the adsorption to be as spontaneous, as well as entropy indication of loss of disorder. Furthermore, the regeneration of 3D GF-CS was utilized in ten consecutive cycles, and the SMZ adsorption capacity did not decline significantly. Additionally, this paper research studied the adsorption energies and how Sulfamethazine adsorbs onto 3D GF-CS were determined by applying the density functional based tight-binding (DFTB) and Monte Carlo simulations at different adsorption positions. The chemical reactivity (local and global) of the free drug was investigated using density functional theory (DFT), namely the B3LYP and PBEPBE functional with the 6-31+G(d,p) basis set in the gas phase and aqueous solution.